Metode Tamyiz untuk Meningkatkan Kemampuan Menerjemah Al-Qur’an di MI Istiqomah Sambas Purbalingga - Kus Risti Yustika; Muh.Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to assess the effectiveness of the Tamyiz method in improving the ability to translate the Al-Qur'an. The study was conducted at MI Istiqomah Sambas Purbalingga by applying field research methods and a qualitative approach. Samples were taken purposively, involving boarding school leaders and teachers as informants, and participatory observation was carried out. The validity of the data is tested through techniques for increasing the persistence of observation, triangulation, implementation analysis, and member checking. Various data analysis techniques, including domain, taxonomic, componential, and cultural theme analysis, were used in this research. The results show that the Tamyiz method has proven to be very effective in teaching Al-Qur'an translation to both beginners and experienced students. With this method, students can translate the Al-Qur’an in just 24 hours.